Coded and uncoded annotations on students’ writing - Rika Riwayatiningsih (Penerbit STKIP PGRI Bangkalan, 2017)
The way on giving corrective feedback whether in coded or uncoded annotations has become a controversy issue among the researcher. Dealing with acquiring language learner errors is an indispensable aspect of classroom pedagogy. The present research primarily focused to examine the role of coded and uncoded annotations in enhancing students writing accuracy of intermediate learners. The quantitative study is used to measure the accuracy of using language mechanics in students’ compositions. Forty male and female of third semester undergraduate students from writing classes in university level participated in the study to determine which kind of corrective feedback affects writing accuracy more. Group one received coded annotations as a written feedback and group two as a control group received uncoded annotations on their writings. The result of the study demonstrated that coded annotations affected students’ performance more.